IMPACT OF CHEMICAL FERTILIZER ON YIELDS AMONG SMALLHOLDER FARMERS: THE CASE OF SIBU SIRE WOREDA, ETHIOPIA - Negese Tamirat; Jemal Abafita (Journal of Smart Economic Growth, 2022)
This study analyzed the impact of technology adoption decisions on the yields of smallholder households in the study area. The data used for the study were obtained from 191 randomly selected sample households in the study area. The average treatment effect of adoption on household yield was estimated by using the propensity score matching method. The propensity score matching estimation showed that the average yields of adopters are greater than that of non-adopters. Since income and income proxy variables have a significant influence on the likelihood of farmers’ adoption income diversification interventions could have a pay-off. The PSM result showed that the positive effects of chemical fertilizer adoption on farm household yields. Since adopters are in a better position; appropriate strategies that increase the intensity of use for the adopter and encourage non-adopter to use chemical fertilizer on their farmland should be promoted and that there is a large scope for enhancing the role of chemical fertilizer in contributing to promoting production.